1994
DOI: 10.3109/01913129409023212
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron Microscopic Identification of Human Parvovirus B19

Abstract: A mildly macerated, hydropic fetus was delivered spontaneously at 25 weeks gestation by a multigravidous black mother. At autopsy, gross and microscopic evidence suggested fetal anemia, and excessive extramedullary erythroblastosis was present generally. Erythroid precursor cells in the pulmonary capillary circulation contained eosinophilic nuclear inclusions consistent with human parvovirus B19 infection. Transmission electron microscopy on osmicated Epon lung sections showed lucent, granular chromatin corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…38 This epidermal fluorescence could reflect incorporation of viral DNA into the keratinocyte genome, leading to antibody production against novel nuclear antigens. As ultrastructural and immunohistochemical studies have shown localization of B19 particles to endothelium, 39,40,41 we postulate that a similar mechanism could render infected endothelium antigenic, accounting for the association of vasculitis and DM with B19 infection in these and previously published cases. 1,2,30,31,34,42 The receptor for B19 on endothelium, P antigen, is also present on erythrocytes and is the presumptive basis of the tropism of the virus for erythrocytes, the basis for the associated hemolytic anemia.…”
Section: Discussionsupporting
confidence: 56%
“…38 This epidermal fluorescence could reflect incorporation of viral DNA into the keratinocyte genome, leading to antibody production against novel nuclear antigens. As ultrastructural and immunohistochemical studies have shown localization of B19 particles to endothelium, 39,40,41 we postulate that a similar mechanism could render infected endothelium antigenic, accounting for the association of vasculitis and DM with B19 infection in these and previously published cases. 1,2,30,31,34,42 The receptor for B19 on endothelium, P antigen, is also present on erythrocytes and is the presumptive basis of the tropism of the virus for erythrocytes, the basis for the associated hemolytic anemia.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, it is possible that the intranuclear inclusions with central clearing seen by light microscopy and demonstrated in formalin-fixed tissues [15][16][17][18] may be a fixation ''artifact'' [26]. The glassy intranuclear inclusions with central clearing, the so-called lantern cells [16,17,19,20], were not observed in any of the cases described in the present study.…”
Section: Discussionmentioning
confidence: 64%
“…1B). There was no condensation of heterochromatin along the periphery of the nucleus of the GPE as seen in histologic sections of formalin-fixed tissues stained with hematoxylin-eosin and in electron microscopic studies [15][16][17][18][19][20]. The nuclei of GPE were round and had fine, uncondensed, uniformly dispersed compact chromatin.…”
Section: Aidsmentioning
confidence: 99%
“…Thus, it is possible that the intranuclear inclusions with central clearing seen by light microscopy and demonstrated in formalin-fixed tissues [15][16][17][18] may be a fixation ''artifact'' [26]. The glassy intranuclear inclusions with central clearing, the so-called lantern cells [16,17,19,20], were not observed in any of the cases described in the present study.…”
Section: Discussionmentioning
confidence: 64%
“…Many of these cells showed 1 to 3 prominent pale to moderate purple nucleoli or inclusions. There was no condensation of heterochromatin along the periphery of the nucleus of the GPE as seen in histologic sections of formalin-fixed tissues stained with hematoxylin-eosin and in electron microscopic studies [15][16][17][18][19][20].…”
Section: Aidsmentioning
confidence: 79%